National tourist guide: Liberia's heartiest welcome to all overseas visitors and investors - Josarma International Business Services Inc. (Monrovia, Liberia: Josarma International Business Services Inc., 1985)
This National Tourist Guide is an open invitation to visit a friendly, so welcoming and most hospitable country - the Republic of Liberia. It covers many prominent areas including physical, political, and tourist
osc 21/05/2019
Ref
Keywords: Tourism; Liberia